Comparison between RT-PCR and the mouse inoculation test for detection of rabies virus in samples kept for long periods under different conditions - Lopes, Marissol Cardoso [UNESP]; Rossignolo Venditti, Leandro Lima [UNESP]; Queiroz, Luzia Helena [UNESP] (Elsevier B.V., 2010)
Antigenic and genetic analyses are important tools for retrospective studies of rabies epidemiology in specific geographical areas. Virus recovery and re-isolation from archival samples conserved for long periods at freezing temperature are essential for these studies. Prolonged preservation, associated with temperature variations, causes significant loss of virus viability. However, molecular tools, such as RT-PCR, can overcome this problem. For this purpose, 95 positive samples stored for 4-13 years at -20 and -80 degrees C were evaluated by mouse inoculation test and RT-PCR. Only 32 (33.6%) of the samples were positive with the mouse inoculation test, while RT-PCR detected the viral genome in 62 (65.3%) samples. When the samples were analyzed in relation to storage period, there was a significant difference in those stored for >10 years, with 59.7% positivity for RT-PCR and 22.1% for mouse inoculation test. The present study confirms the significance of RT-PCR for detection of viral genomes in archival samples, including those in an apparent state of decomposition. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Epidemiology; Rabies virus genome; Virus viability; Molecular biology; Frozen samples